Simulation-Based Learning for Hardware and Physical Security: A Case Study in Engineering Education - Wulan Sari , Annisa (International Journal of Research and Applied Technology (INJURATECH), 2023)
In an era where cybersecurity threats increasingly target hardware components, equipping students with practical skills in hardware and physical security is crucial. This paper presents a case study on the implementation of simulation-based learning methods within an engineering education context. By integrating interactive simulations that mimic real-world physical attacks and defense mechanisms, students are able to experience and understand critical concepts such as tamper detection, access control, and secure hardware design. The study evaluates the effectiveness of simulation-based modules compared to traditional theoretical approaches through surveys and performance assessments. Results indicate that students exposed to simulations demonstrate higher engagement, deeper conceptual understanding, and improved problem-solving skills in hardware security scenarios. This research highlights the importance of adopting innovative, hands-on learning techniques to better prepare the next generation of cybersecurity professionals